Vascular health in the ageing athlete - DeVan, A. E.; Seals, D. R. (The biomedical basis of elite performance. 19-21 March 2012, London, UK. Abstracts & Manuscripts, 2012)
The demographics of ageing are changing dramatically such that there will be many more older adults in the near future. This setting is projected to produce a new `boomer-driven` epidemic of physiological dysfunction, disability and risk of chronic degenerative disorders, including cardiovascular diseases. Standing out against this dreary biomedical forecast are Masters athletes, a group of middle-aged and older adults who engage in regular vigorous physical training and competitive sport. Compared with their sedentary/less active (untrained) peers, Masters athletes who perform endurance training-based activities demonstrate a more favourable arterial function-structure phenotype, including lower large elastic artery stiffness, enhanced vascular endothelial function and less arterial wall hypertrophy. As such, they may represent an exemplary model of healthy or `successful` vascular ageing. In contrast, Masters athletes engaged primarily/exclusively in intensive resistance training exhibit less favourable arterial function-structure than their endurance-trained peers and, in some instances, untrained adults. These different arterial properties are probably explained in large part by the different intravascular mechanical forces generated during endurance versus resistance exercise-related training activities. The more favourable arterial function-structure profile ofMasters endurance athletes may contribute to their low risk of clinical cardiovascular diseases.